2017
DOI: 10.1080/1046560x.2017.1415615
|View full text |Cite
|
Sign up to set email alerts
|

Genuine Faculty-Mentored Research Experiences for In-Service Science Teachers: Increases in Science Knowledge, Perception, and Confidence Levels

Abstract: The overall purpose of this multifocused study was to explore how participation in genuine mentored scientific research experiences impacts in-service science teachers and the knowledge and skills needed for their own science teaching. The research experiences resulted from a partnership between the University of Nebraska at Omaha and the Omaha Public School District. This Teacher

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The literature on short-term research experiences such as RETs demonstrates that teachers' participation in the research experiences with scientists can improve their understandings of scientific inquiry (Bahbah et al, 2013;Blanchard & Sampson, 2018;Buxner, 2014;Herrington et al, 2016), perceptions of inquiry (Peters-Burton et al, 2015), confidence in science and inquiry (Cutucache et al, 2017), and views of scientific inquiry (Hughes et al, 2012). However, it has also been demonstrated that the teachers' conceptions of the practices of science remain naïve even after completing an RET (Ozalp, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on short-term research experiences such as RETs demonstrates that teachers' participation in the research experiences with scientists can improve their understandings of scientific inquiry (Bahbah et al, 2013;Blanchard & Sampson, 2018;Buxner, 2014;Herrington et al, 2016), perceptions of inquiry (Peters-Burton et al, 2015), confidence in science and inquiry (Cutucache et al, 2017), and views of scientific inquiry (Hughes et al, 2012). However, it has also been demonstrated that the teachers' conceptions of the practices of science remain naïve even after completing an RET (Ozalp, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scientist–teacher partnerships encompass a broad range of activities in which scientists and teachers interact with the purpose of improving science education. These activities may entail one-time visits to classrooms by scientists, partnering of scientists and teachers, , professional-development programs developed in coordination with scientists, and research experiences for teachers (RETs). , The primary purpose of many scientist–teacher partnerships is to support the professional development of teachers and thereby support student science learning. Specifically, scientist–teacher partnerships may focus on developing understanding of scientific inquiry and the use of inquiry in teaching, , developing understanding of the nature of science, , and developing content knowledge. , Scientist–teacher partnerships also provide opportunities for teachers and students to learn more about current science, scientific research, and science careers . For example, the National Science Foundation (NSF) emphasizes the role of RETs in bringing current science and engineering into the classroom by enhancing “the professional development of K–12 science educators through research experience at the emerging frontiers of science in order to bring new knowledge into the classroom” while enabling “K–12 STEM teachers and community college faculty to translate their research experiences and new knowledge gained in university settings into their classroom activities”…”
Section: Related Literaturementioning
confidence: 99%
“…Students of high school science teachers who engaged in summer research experience had improved scores in standardized tests after their teachers participated in research (Silverstein et al, 2009). High school science teachers participating in mentored research experiences report improvements in science content knowledge, perceptions and confidence levels in process and content that influence their own science teaching and translatability to their students (Cutucache et al, 2017). Furthermore, such experiences inculcate positive networks and collaborations between researchers, teachers, and schools.…”
Section: Introductionmentioning
confidence: 99%